Binding pancreaticojejunostomy – a safe and reliable anastomosis procedure - Peng, SY (2004)
Background Over the past one hundred years, the development of pancreaticoduodenectomy (PD) has always involved the struggle against pancreatic leakage. Until now, leakage of the pancreatic anastomosis has remained a common and serious complication after PD. Various methods of dealing with the pancreatic stump for prevention of pancreatic anastomotic leakage have been described. No matter which method is used, however, pancreatic anastomotic leakage is still most likely to occur when anastomosis involves a normal and soft pancreas. Methods To perform a safe and reliable pancreaticoenteric anastomosis, we investigated the risk factors and potential mechanisms of occurrence of pancreatic leakage, including leakage from the needle hole and from the seam between two anastomosed structures, blood supply to the anastomosis and tension at the anastomosis. Based on these findings, we established a new pancreaticoenteric anastomosis procedure – binding pancreaticojejunostomy. The unique aspects of this procedure are as follows. The sero-muscular sheath of jejunum is bound to the invaginated pancreatic stump, so as to seal the gap between them; mucosa of the segment of jejunum that would eventually be in contact with the pancreatic stump is destroyed either chemically or by electric coagulation to promote healing. There is no needle hole on the jejunal surface of the anastomotic site. Results From 1996 to 2003, a total of 227 consecutive patients were treated with this type of pancreaticojejunostomy in this institution. None of the patients developed a pancreatic anastomotic leak. Discussion Binding pancreaticojejunostomy is a safe and reliable anastomotic procedure to effectively minimize leakage even when the texture of the pancreas is soft and normal.